PREDICTING OF TSUNAMI HAZARD AREA USING SATELLITE REMOTE SENSING DATA AND GIS - Agus Suharyanto; A Pujiraharjo; A Yudono; K Murakami; C Deguchi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Brawijaya, 2014)
Tsunami is very important phenomena in the disaster management problems. Based on the tsunami was occurred in Aceh Indonesia on December 26, 2004 killed more than 200.000 peoples, the tsunami disaster management become very important to study. According to the geological data, area of east Java Ocean has high potential of earthquake. The history shows that there are many time tsunami occurred in east Java. In 1994 the tsunami was occurred in Kabupaten Banyuwangi (Banyuwangi Prefecture) beach and was killed 240 peoples. To minimize the effect of tsunami hazard, the study of tsunami disaster management is necessary. The first step of study is predicting of area in along shoreline of east Java province, Indonesia. The study based on the topographic map in scale 1:25.000, SPOT HRV satellite imageries scanned on 2009. Geographic Information System (GIS) technology was used in this research. The tsunami runup was simulated using COMCORT. From the analyzed results it can be seen that there are five important areas have dangerous effect of tsunami. The areas from west to east are Pacitan city, Prigi fishermen residential area, Ambulu residential area, Grajagan tourist’s area, and several small residential areas along the shoreline. From this study it can be concluded that the satellite remote sensing data combined with the GIS is powerful to analyze the inundated area due to the tsunami hazard. To analyze the evacuation route and place which takes in refugees or shelter area topographic map, road physical condition, number of residential, infrastructure along evacuation route data are necessary.